Building of Sacral Objects as a Path to Salvation: Examples from the Serbian Hagiographic Literature - Milojević, Snežana J. (Collection of Papers of the Faculty of Philosophy in Priština, 2020)
Starting from the postulate of Christian doctrine that every creation comes from the Holy Spirit, we have applied the already known principles of Theopoetics to the construction of churches and monasteries, through the topos of the struggle in God’s name. We have found confirmation for this form of the preconditioning of human salvation in the hagiographical texts of old Serbian literature. In connection with the given topic, we pointed out timeliness (timely dedication to this God-pleasing work), as a key element which narratively shapes the soteriological motivation of this type of human feat. Speaking about the aesthetic correlation of the building of churches and monasteries, we pointed out the complexity of medieval aesthetics based on Christian doctrine.
Keywords: building of churches and monasteries; motive of not being late; metaphysical aesthetics; heavenly Jerusalem